Taxonomy and bioacoustics of some katydids of the tribes Meconematini and Phisidini (Orthoptera, Tettigoniidae, Meconematinae) from eastern Sabah - Tan, Ming Kai; Jin, Xingbao; Wang, Hanqiang; Japir, Razy; Chung, Arthur Y.c. (Zootaxa, 2022)
A new species of Meconematini is described from Tabin Wildlife Reserve in eastern Sabah: Cercoteratura repens sp. nov. This is the first report of the genus Cercoteratura in Sabah. Two species of Phisidini, Carliphisis acutipennis (Carl, 1908) and Neophisis (Indophisis) longipennis Jin, 1992, are reported in eastern Sabah for the first time. The calling song of Neophisis (Indophisis) longipennis with a near-complete ultrasonic spectrum is also described.